2021
DOI: 10.1186/s40723-021-00091-9
|View full text |Cite
|
Sign up to set email alerts
|

How stable is program quality in child care centre classrooms?

Abstract: In the Early Childhood Education and Care (ECEC) sector there is a move to reduce oversight costs by reducing the frequency of quality assessments in providers who score highly consistently across time. However, virtually nothing is known about the stability of ECEC quality assessments over time. Using a validated measure of overall classroom quality, we examined stability of quality in a sample of over 1000 classrooms in licensed child care centres in Toronto, Canada over a 3-year period. Multilevel mixed-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In many countries, the ECEC sector operates as a mixed-market system notable for its diversity, ranging from single-service providers to large organisations that operate multi-site centres. Diversity in provider size is characteristic of both for-profit and not-for-profit services in countries such as Australia (Brennan & Fenech, 2014 ), Canada (Varmuza et al, 2021 ) and Finland (Mäntyjärvi & Puroila, 2019 ), with some research suggesting that provider size can impact quality. For example, a national survey of Australian educators showed that centres that were part of a large corporate chain were rated significantly lower on having time to develop individual relationships with children than centres operated by small private operators (Rush, 2006 ).…”
Section: Systemic Influences On Quality In Ececmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, the ECEC sector operates as a mixed-market system notable for its diversity, ranging from single-service providers to large organisations that operate multi-site centres. Diversity in provider size is characteristic of both for-profit and not-for-profit services in countries such as Australia (Brennan & Fenech, 2014 ), Canada (Varmuza et al, 2021 ) and Finland (Mäntyjärvi & Puroila, 2019 ), with some research suggesting that provider size can impact quality. For example, a national survey of Australian educators showed that centres that were part of a large corporate chain were rated significantly lower on having time to develop individual relationships with children than centres operated by small private operators (Rush, 2006 ).…”
Section: Systemic Influences On Quality In Ececmentioning
confidence: 99%
“…In addition, observations of positive caregiving gathered in a large US study have shown lower scores in for-profit multi-site organisations compared to independent for-profit services, for some but not all age groups (Sosinsky et al, 2007 ). More recently, Varmuza et al ( 2021 ) have examined three years of Canadian QRIS data for single and multi-site, for-profit and not-for-profit providers using the Assessment for Quality Improvement (AQI). While there were no consistent differences in annual comparisons of quality by the size of provider, multi-site for-profit operators showed increasing AQI ratings over time.…”
Section: Systemic Influences On Quality In Ececmentioning
confidence: 99%